ESL Teachers' Perceptions About English Learners' Reading Motivation. (November 2016) - Protacio, Maria Selena; Jang, Bong Gee
The role of motivation in engaging students in reading activities and thus improving their reading achievement has been widely reported for the past decades. However, despite the increasing numbers of English learners (ELs) in the United States, little is known about how teachers perceive their motivation to read. Focus group methodology was used in this study to explore English as a second language teachers' perceptions of ELs' reading motivation. Three major themes that emerged from our qualitative analysis were (a) accessible texts, (b) self-concept, and (c) fitting in. The implications for both future research and classroom instruction are provided.